2011
DOI: 10.1002/ptr.3445
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Expression Analysis of the Effect of the Chinese Patent Medicine Zilongjin Tablet on Four Human Lung Carcinoma Cell Lines

Abstract: Zilongjin (ZLJ) tablet, which is a traditional Chinese medicine, has been approved as a new anti-tumor drug by the State Food and Drug Administration of China; however, its anti-cancer mechanisms remain elusive. The goal of this study was to investigate the underlying anti-cancer activities of ZLJ tablet in vitro. In this study, four lung cancer cell lines, A549, H446, H460 and H520, were treated with 2.2 mg/mL of ZLJ solution for 24 h at 37 °C under 5% CO(2) . RNA was isolated and a microarray experiment usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Microarray based gene expression analysis of four different lung cancer cell lines treated by Zilongjin showed that 170 genes were upregulated and 313 were downregulated by the drug. Of these 483 genes, eleven genes including HELLS , JUN , XIAP , MCM6 , CDKN2C , CCNE2 , HN1L , TFDP2 , CCNG2 , GADD45A , and CDKN1A were found to be involved in cancer-related pathways such as apoptosis, cell cycle, and MAPK cascade [96]. …”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…Microarray based gene expression analysis of four different lung cancer cell lines treated by Zilongjin showed that 170 genes were upregulated and 313 were downregulated by the drug. Of these 483 genes, eleven genes including HELLS , JUN , XIAP , MCM6 , CDKN2C , CCNE2 , HN1L , TFDP2 , CCNG2 , GADD45A , and CDKN1A were found to be involved in cancer-related pathways such as apoptosis, cell cycle, and MAPK cascade [96]. …”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…Rigorous and systematic evaluations are, however, necessary to establish the efficacy of herbal formulas and transform traditional herbal practices into sciencebased medicines. [13][14][15][16][17] In the present article, we evaluated the anticancer activity of Ke formula, which has been shown to be effective in the clinic. The crude formula used in this study followed TCM treatment principles based on syndrome differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Typically they would include those that have been used for decades or hundreds of years and still nationally or very widely used in China or other countries. Many patent drugs [40, 41] and classical formulas will fall into this group. We suggest including in category 1 also new CHM formulas that have already been evaluated in randomized controlled trials.…”
Section: Chms Vary In Certainty Of Their Safety and Efficacymentioning
confidence: 99%